Risk factors, diagnosis and management of bone stress injuries in adolescent athletes: a narrative review - Beck, B.; Drysdale, L. (Sports, 2021)
Physical activity is known to be beneficial for bone; however, some athletes who train intensely are at risk of bone stress injury (BSI). Incidence in adolescent athlete populations is between 3.9 and 19% with recurrence rates as high as 21%. Participation in physical training can be highly skeletally demanding, particularly during periods of rapid growth in adolescence, and when competition and training demands are heaviest. Sports involving running and jumping are associated with a higher incidence of BSI and some athletes appear to be more susceptible than others. Maintaining a very lean physique in aesthetic sports (gymnastics, figure skating and ballet) or a prolonged negative energy balance in extreme endurance events (long distance running and triathlon) may compound the risk of BSI with repetitive mechanical loading of bone, due to the additional negative effects of hormonal disturbances. The following review presents a summary of the epidemiology of BSI in the adolescent athlete, risk factors for BSI (physical and behavioural characteristics, energy balance and hormone disruption, growth velocity, sport-specific risk, training load, etc.), prevention and management strategies.